Energy use by air taxis and drones for parcel delivery, is it practical? Is it sustainable?. (10th April 2018) - Rez, Peter
ABSTRACT: Abstract : Aircraft that take off and land vertically with rotors or horizontal propellers like drones use more energy than conventional aircraft whose lift is provided by wings. Drones with propellers are less efficient than helicopters with large rotors. The poor energy density of batteries compared to hydrocarbon fuels limits the range and endurance of the electrically powered aircraft. Although the ratio of the mass of payload and fuel (or battery) to the total aircraft mass for the proposed Amazon drone is not that different from the same ratio for a Boeing 747, the range and time in the air is very much less. In principle, a conventional aircraft powered by photovoltaic panels covering a wing with a span of 6 m could match the performance of the proposed Amazon drone. Amazon has proposed delivering packages by an electrically powered drone capable of vertical take off and landing. By comparison with helicopters, the energy needed to move a 2.5 kg package is estimated to be more than 130 times the energy used in delivering the same package in a small delivery truck. By comparison, a conventional airplane with the same mass could, in principle, be powered by photovoltaic panels, covering the wings, and it would use an energy equivalent to about 3 times the energy used by a small delivery truck. Based on the performance of existing small helicopters, the analysis shows that an electrically powered air taxi would only be able to make journeys of 10 min or less. Vertical take-off and landing add to energy requirements, and drones using a large number of propellers are less efficient than helicopters. The major limitation, not surprisingly, is the poor energy density of batteries compared to liquid hydrocarbon fuels.